Hybrid nanofluid, coating, liquid heat-preservation storage and transportation equipment and preparation method of liquid heat-preservation storage and transportation equipment
By using a hybrid nanofluid coating prepared in combination with functionalized multi-wall carbon nanotubes, alumina particles and titanium carbides, the problem of low thermal management efficiency of liquid insulation storage and transportation equipment in extreme environments is solved, and efficient thermal conductivity and long-term stability are achieved.
Patent Information
- Application Number
- CN202411875084.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing liquid insulation storage and transportation equipment has problems such as insufficient heat dissipation measures and low thermal management efficiency, especially in extreme temperatures and complex environments.
Using the preparation method of hybrid nanofluid, a hybrid nanofluid coating with high thermal conductivity, chemical stability and synergistic effects is formed by a combination of functionalized multi-wall carbon nanotubes, stable alumina particles and titanium carbides.
It significantly improves the thermal conductivity and weather resistance of liquid insulation storage and transportation equipment, ensures excellent thermal management performance and long-term stability in extreme environments, and reduces the evaporation loss of liquids and the difficulty of temperature control.
Smart Images

Figure CN119684832A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nano materials and coatings, and more specifically to a hybrid nano fluid, coating, liquid heat preservation storage and transportation equipment and a preparation method thereof. Background Art
[0002] Liquid hydrogen is a clean and efficient energy carrier. Its extremely low storage temperature (-253°C) places strict demands on temperature control during transportation and storage. In order to solve the temperature control problem in liquid hydrogen transportation, a variety of technical means have been adopted, such as vacuum multi-layer insulation design and traditional thermal insulation coating.
[0003] The vacuum multi-layer insulation design uses aluminum alloy coating, epoxy resin coating and other materials as the external coating. This method can effectively isolate external heat, but there are problems such as the vacuum layer being easily damaged and the coating surface being easily oxidized, which will lead to increased liquid hydrogen evaporation losses, a sharp drop in thermal insulation performance, and certain safety hazards. Traditional thermal insulation coatings, such as aluminum alloy coatings and epoxy resin coatings, have problems such as poor adhesion, insufficient high temperature resistance, and poor long-term stability in actual applications. Summary of the invention
[0004] The present invention provides a hybrid nanofluid, a coating, a liquid heat preservation storage and transportation device and a preparation method thereof, which are used to solve the problems of insufficient heat dissipation measures and low thermal management efficiency of the liquid heat preservation storage and transportation device in the prior art.
[0005] In a first aspect, the present invention provides a method for preparing a hybrid nanofluid, comprising the following steps: functionalizing multi-walled carbon nanotubes (MWCNTs) with sodium N-methyl-N-octadecyl taurate (SMDS) to obtain functionalized multi-walled carbon nanotubes (whose microstructure is as follows: Figure 1 ); adding bisaminopropyl polyether to an aqueous suspension of aluminum oxide (Al2O3), stirring, centrifuging, and drying in sequence to obtain stable aluminum oxide particles; mixing the functionalized multi-walled carbon nanotubes, the stable aluminum oxide particles, and titanium carbide (Ti3C2T x ) is added into the base liquid and dispersed evenly to obtain the hybrid nanofluid.
[0006] In the raw materials for preparing the hybrid nanofluid provided by the present invention, MWCNTs have excellent axial thermal conductivity, Al2O3 has excellent chemical stability, Ti3C2T x The invention has excellent two-dimensional structure thermal conductivity. The invention uses SMDS to perform functionalization treatment on MWCNTs to enhance the compatibility of MWCNTs with liquid matrix.
[0007] The latent heat characteristics of the hybrid nanofluid were analyzed by thermal property research. Differential scanning calorimetry (DSC, used to determine the thermal stability of the material) and thermogravimetric analysis (TGA, used to evaluate the mass loss of the coating at high temperature) were used to evaluate the thermal characteristics of the prepared hybrid nanofluid. The results showed that the prepared hybrid nanofluid can maintain stable thermal conductivity at high temperatures. The hybrid nanofluid was characterized by Fourier transform infrared spectroscopy (FTIR) technology to analyze its surface chemical structure and functional treatment effect. The Ti3C2T x The synergistic effect between MWCNTs and Al2O3 improves the chemical stability and thermal conductivity of the material.
[0008] As a possible implementation, the base liquid is one of water and ethanol or a combination of the two; and / or, the mass ratio of the functionalized multi-walled carbon nanotubes, the stable alumina particles and titanium carbide is 1:1 to 2:2 to 3; and / or, the uniform dispersion is through ultrasonic treatment. As a possible implementation, the functionalization treatment includes the steps of: mixing the multi-walled carbon nanotubes with a 0.1 mol / L solution of sodium N-methyl-N-octadecyl taurate, sequentially performing ultrasonic dispersion, stirring at room temperature, suction filtration, washing operations, and drying to constant weight to obtain the functionalized multi-walled carbon nanotubes; and / or, the preparation process of the stable alumina particles includes the steps of: adding bisaminopropyl polyether to a suspension of alumina particles and deionized water at a mass ratio of 1:5, stirring at a rate of 300 rpm at 60°C for 1 hour, centrifuging, and drying to obtain the stable alumina particles.
[0009] In a second aspect, the present invention provides a hybrid nanofluid prepared by the preparation method described in any possible implementation of the first aspect.
[0010] In a third aspect, the present invention provides a hybrid nanofluid coating, the preparation process of which includes the steps of: mixing the hybrid nanofluid described in claim 4, epoxy resin and bisaminopropyl polyether, adding a dispersant, dispersing evenly, and evaporating the solvent at 50-70°C to form a coating component A; adding a curing agent, propylene glycol methyl ether, acrylic acid and polysiloxane to an organic solvent, ultrasonically dispersing evenly to form a coating component B; and mixing the coating component A and the coating component B evenly to obtain the hybrid nanofluid coating.
[0011] As a possible implementation, the dispersant is a nanosilane coating material; and / or the curing agent is an isocyanate; and / or the organic solvent is ethanol; and / or the mass ratio of the hybrid nanofluid, the epoxy resin, the bisaminopropyl polyether and the dispersant is 28:70:0.5:1.5; and / or the mass ratio of the curing agent, the propylene glycol methyl ether, the acrylic acid and the polysiloxane is 20:3:0.7:0.5; and / or the mass ratio of the coating component A and the coating component B is 7:3.
[0012] In a fourth aspect, the present invention provides an application of a hybrid nanofluid prepared by the preparation method described in any possible implementation of the first aspect, or a hybrid nanofluid described in any possible implementation of the second aspect, or a hybrid nanofluid coating described in any possible implementation of the third aspect in liquid insulation storage and transportation equipment.
[0013] In a fifth aspect, the present invention provides a liquid thermal insulation storage and transportation equipment, the outer surface of which is coated with the hybrid nanofluid coating described in the fourth aspect; the outer surface of the hybrid nanofluid coating is coated with a topcoat.
[0014] As a possible implementation, the coating step of the hybrid nanofluid coating includes: spraying at a pressure of 0.3 MPa and a thickness of 50 to 150 μm, and then drying at a temperature of 60° C. until the hybrid nanofluid coating is fully cured.
[0015] As a possible implementation, the preparation step of the topcoat includes: mixing a polyurethane resin with modified polyvinyl alcohol, adding a thickener and a solvent, and stirring at 60° C. for 1 hour to obtain the topcoat.
[0016] As a possible implementation, the liquid insulation storage and transportation equipment includes but is not limited to liquid hydrogen / liquid nitrogen / liquid oxygen transport vehicles, liquid hydrogen / liquid nitrogen / liquid oxygen storage tanks, and liquid hydrogen / liquid nitrogen / liquid oxygen storage tanks.
[0017] In the preparation of the hybrid nanofluid provided by the present invention, the three raw materials show a synergistic effect in the composite, which significantly improves the thermal conductivity, mechanical strength and chemical stability of the target product; the materials used are recyclable, non-toxic and environmentally friendly, in line with the concept of green development, and will not release harmful substances, especially in high temperature environments.
[0018] The hybrid nanofluid coating provided by the present invention has a high thermal conductivity inside due to the extremely small size of the nanoparticles, and can quickly transfer and dissipate external heat; by modifying the surface of the nanofluid, the stability, thermal conductivity, weather resistance, etc. of the nanocoating are enhanced, and the hybrid nanofluid coating exhibits excellent high temperature resistance, weather resistance and long-term stability, and can maintain excellent performance under extremely low temperatures (-253°C) and complex conditions during liquid storage and transportation, ensuring efficient temperature control and safe operation. At the same time, the hybrid nanofluid coating exhibits low energy consumption, sustainability and long-term reliability in preparation and application, meets the high efficiency and environmental protection requirements of liquid storage and transportation, and has broad application prospects.
[0019] The liquid insulation storage and transportation equipment prepared with the hybrid nanofluid coating provided by the present invention has excellent thermal conductivity, dispersibility and weather resistance, and significantly improves its performance under extreme environmental conditions (extremely high temperature, extremely low temperature, etc.). The liquid insulation storage and transportation equipment can operate stably for a long time in complex climate environments such as high temperature, humidity, and ultraviolet radiation, and exhibits excellent anti-aging ability and thermal management performance. It can effectively block external heat transfer and effectively prevent the evaporation loss of liquid inside the liquid insulation storage and transportation equipment caused by ambient temperature fluctuations, thereby ensuring the internal low-temperature stability and improving storage and transportation safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 Schematic diagram of the microstructure of functionalized multi-walled carbon nanotubes provided in an embodiment of the present invention.
[0022] Figure 2 A flow chart for preparing a hybrid nanofluid coating provided in an embodiment of the present invention.
[0023] Figure 3 This is a scanning electron microscope (SEM) image of the hybrid nanofluid provided in an embodiment of the present invention.
[0024] Figure 4 The embodiment of the present invention provides the influence of temperature on the thermal conductivity of different nanomaterials. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In order to solve the problems of insufficient heat dissipation measures and low thermal management efficiency of liquid thermal insulation storage and transportation equipment in the prior art, the embodiments of the present invention provide a hybrid nanofluid, a coating, a liquid thermal insulation storage and transportation equipment and a preparation method thereof.
[0027] The present application example provides a preparation experiment of a hybrid nanofluid and uses the prepared hybrid nanofluid I as an example for SEM characterization. It can be seen that the structure of the hybrid nanofluid I is more compact, which is conducive to the rapid dissipation of heat. The prepared hybrid nanofluid is subjected to comparative characterization of various physical and chemical properties. It can be seen that the hybrid nanofluid provided by the present invention has an increase in thermal conductivity of about 36%, a thinner coating thickness, which is conducive to improving thermal conductivity, a shortened curing time of about 30%, and a higher efficiency. The raw materials are all environmentally friendly and recyclable raw materials, which conform to the concept of green energy, and the service life is increased by about 50%.
[0028] Furthermore, the embodiment of the present invention provides a preparation experiment of a hybrid nanofluid coating and verifies the effect. It can be seen that the hybrid nanofluid coating provided by the present invention has excellent thermal conductivity stability and excellent thermal insulation performance, ensuring that the liquid hydrogen storage tank is not significantly affected by changes in external environmental temperature. Whether in an extremely high temperature, low temperature, humid heat or strong ultraviolet radiation environment, the coating can maintain its thermal management effect without obvious performance degradation. In addition, the hybrid nanofluid coating provided by the present invention has significant hydrophilicity, which helps to reduce water droplet accumulation and improve heat dissipation performance. Its thermal conductivity is more than 30% higher than that of traditional coatings, which significantly improves thermal conductivity, can effectively alleviate the problem of liquid hydrogen evaporation caused by temperature increase, and can effectively block external heat (such as solar radiation, ambient temperature fluctuations, etc.) from being conducted to the inside of the liquid hydrogen storage tank, maintaining the ultra-low temperature (-253°C) stability of the liquid hydrogen storage tank. It has excellent anti-corrosion properties and can provide reliable anti-corrosion protection under normal conditions. It can also maintain long-term stability and reliability in extreme environments such as low temperature, humidity, and highly corrosive liquids, thereby significantly extending the service life of liquid hydrogen transport vehicles and greatly improving the safety and economy of the transportation process.
[0029] The technical solution of the present invention will be further described below in conjunction with specific embodiments.
[0030] Example 1
[0031] This embodiment provides a preparation experiment of a hybrid nanofluid.
[0032] according to Figure 2 In the first three steps of the process shown, MWCNTs were treated with a 0.1 mol / L SMDS solution, ultrasonically dispersed for 30 minutes, stirred at room temperature for 2 hours, filtered, washed with deionized water until neutral, and dried to constant weight to obtain functionalized MWCNTs; a suspension of alumina particles and deionized water (mass ratio 1:5) was stirred at 300 rpm at 60°C for 1 hour, centrifuged, and dried to obtain stable alumina particles.
[0033] 5g functionalized MWCNTs, 5g Ti3C2T x and 10 g of stable alumina particles were mixed in 1000 mL of base liquid I (ethylene glycol), and treated with ultrasonic dispersion (frequency 40 kHz, power 300 W) at 70 ° C for 1 hour to obtain hybrid nanofluid I. The prepared hybrid nanofluid I was scanned by SEM, and the following was obtained: Figure 3 From the results shown, it can be seen that the structure of hybrid nanofluid I is more compact, which is conducive to the rapid dissipation of heat.
[0034] 5g functionalized MWCNTs, 10g Ti3C2T x It was mixed with 15 g of stable alumina particles in base liquid II (deionized water: ethylene glycol volume ratio = 1:1), and treated with ultrasonic dispersion (frequency 40 kHz, power 600 W) at 70°C for 6 hours to obtain hybrid nanofluid II.
[0035] 5 g of functionalized MWCNTs and 10 g of stable alumina particles were mixed in 1000 mL of base liquid I (ethylene glycol) and treated with ultrasonic dispersion (frequency 40 kHz, power 300 W) at 70° C. for 1 hour to obtain hybrid nanofluid III.
[0036] The thermal conductivity of the prepared hybrid nanofluids I and III was measured, and the results were as follows: Figure 4 From the results shown, it can be seen that the thermal conductivity of hybrid nanofluid I changes faster with temperature, so its thermal conductivity is higher, which is conducive to adapting to external temperature changes to improve temperature stability.
[0037] The prepared hybrid nanofluids I and III were subjected to performance tests, and the results shown in Table 1 were obtained.
[0038] Table 1 Characterization results of hybrid nanofluid performance
[0039] Performance Indicators Hybrid Nanofluids I Hybrid Nanofluids Ⅲ Particle size (nm) 10~50 60~80 Thermal conductivity (W / m·k) 75 55 Coating thickness (μm) 50~120 60~150 Curing time (h) 3~5 6~8 Working temperature(℃) -253~100 -200~70 Raw material properties Environmentally friendly and recyclable Some are not recyclable Service life (y) ≥15 ≥10 Reunion No agglomeration, no sedimentation No agglomeration, no sedimentation
[0040] Depend on Figure 1It can be seen that compared with hybrid nanofluid III, the thermal conductivity of hybrid nanofluid I is increased by about 36%, the coating thickness is thinner, which is conducive to improving thermal conductivity, the curing time is shortened by about 30%, and the efficiency is higher. The raw materials are all environmentally friendly and recyclable raw materials, which conforms to the concept of green energy, and the service life is increased by about 50%. x It plays an important role in improving the performance of hybrid nanofluids.
[0041] Example 2
[0042] This embodiment provides a preparation experiment of a hybrid nanofluid coating.
[0043] according to Figure 2 In the latter two steps of the process shown, the hybrid nanofluid coating I (concentration of 3%), epoxy resin (mass fraction of 70%) and Jeffamine (mass fraction of 0.5%) prepared in Example 1 are mixed, and nanosilane coating material (mass fraction of 1.5%) is added as a dispersant, and ultrasonic dispersion is performed for 2 hours; the temperature is raised to 60°C, and the solvent ethanol is stirred and evaporated to form a modified coating primer component A. Isocyanate (mass fraction of 20%) is used as a curing agent, propylene glycol methyl ether (mass fraction of 3%), acrylic acid (mass fraction of 0.7%) and polysiloxane (mass fraction of 0.5%) are mixed, and a solvent is added and ultrasonic dispersion is performed uniformly to form a coating component B. The modified coating primer component A and the coating component B are mixed at a mass ratio of 7:3 and stirred uniformly to obtain a hybrid nanofluid coating I.
[0044] The hybrid nanofluid II (concentration of 1.5%) prepared in Example 1, epoxy resin (mass fraction of 75%) and Jeffamine (mass fraction of 0.5%) were mixed, and nanosilane coating material (mass fraction of 1.5%) was added as a dispersant, and ultrasonic dispersion was performed for 2 hours; the temperature was raised to 60°C, and the solvent was evaporated by stirring to form a modified coating primer component A. Isocyanate (mass fraction of 20%) was used as a curing agent, propylene glycol methyl ether (mass fraction of 3%), acrylic acid (mass fraction of 0.7%) and polysiloxane (mass fraction of 0.5%) were mixed, and the solvent was added and ultrasonic dispersion was performed uniformly to form a coating component B. The modified coating primer component A and the coating component B were mixed at a mass ratio of 7:3, and stirred uniformly to obtain a hybrid nanofluid coating II.
[0045] Example 3
[0046] This embodiment provides an application effect verification experiment of a hybrid nanofluid coating.
[0047] The application scenarios of the liquid insulation storage and transportation equipment mentioned in this embodiment include but are not limited to liquid hydrogen / liquid nitrogen / liquid oxygen transport vehicles, liquid hydrogen / liquid nitrogen / liquid oxygen storage tanks, and liquid hydrogen / liquid nitrogen / liquid oxygen storage tanks. In this embodiment, various tests were carried out using liquid hydrogen storage tanks as an example. The topcoat preparation process used in this embodiment includes: mixing a polyurethane resin (mass fraction 55%) and a modified polyvinyl alcohol (mass fraction 20%) in a mass ratio of 1:0.2, adding a thickener (mass fraction 15%) and a solvent (mass fraction 10%), stirring at 60°C for 1 hour, and preparing a topcoat. The topcoat has excellent smoothness and hydrophilicity, which can enhance the weather resistance and long-term stability of the coating.
[0048] The hybrid nanofluid coating I in Example 2 was uniformly applied to the outer surface of the liquid hydrogen storage tank by spraying, with a spraying pressure of 0.3 MPa, a spraying distance of 10 cm, and a coating thickness of 50 μm. After the coating was completed, it was dried in a drying oven at 60°C for 6 hours until the coating was fully cured. Then, the topcoat was applied and dried to obtain the fluid test model I.
[0049] The hybrid nanofluid coating II in Example 2 was uniformly applied to the outer surface of the liquid hydrogen storage tank by spraying, with a spraying pressure of 0.3 MPa, a spraying distance of 10 cm, and a coating thickness of 100 μm. After coating, it was dried in a drying oven at 60°C for 12 hours until the coating was fully cured. Then, the topcoat was applied and dried to obtain the fluid test model II.
[0050] The topcoat is applied to the outer surface of the liquid hydrogen storage tank, dried and solidified, and a fluid test model III is obtained.
[0051] The commercial coating (polyurethane coating) was uniformly applied to the outer surface of the liquid hydrogen storage tank by spraying, with a spraying pressure of 0.3 MPa, a spraying distance of 10 cm, and a coating thickness of 100 μm. After coating, it was dried in a drying oven at 60°C for 12 hours until the coating was fully cured. Then, the topcoat was applied and dried to obtain the fluid test model IV.
[0052] Alumina solution (concentration of 10%) was uniformly applied to the outer surface of the liquid hydrogen storage tank by spraying, with a spraying pressure of 0.3MPa, a spraying distance of 10cm, and a coating thickness of 100μm. After coating, it was dried in a drying oven at 60°C for 12h until the coating was fully cured. Then, the topcoat was applied and dried and cured to obtain the fluid test model V.
[0053] The fluid test model I and the fluid test model II were placed in a temperature range of -196°C to 150°C to test the thermal conduction stability. The results showed that the surface temperature fluctuations of the fluid test model I and the fluid test model II were both within 5°C. It can be seen that the hybrid nanofluid coating I and the hybrid nanofluid coating II have excellent thermal conduction stability and excellent thermal insulation properties, ensuring that the liquid hydrogen storage tank is not significantly affected by changes in external ambient temperature. Whether in extremely high temperature, low temperature, humid heat or strong ultraviolet radiation environment, the coating can maintain its thermal management effect without obvious performance degradation.
[0054] The physical and chemical properties of fluid test model I to fluid test model V were characterized, and the results shown in Table 2 were obtained.
[0055] Table 2 Fluid test model performance characterization results
[0056]
[0057] As shown in Table 2, compared with fluid test model III, hybrid nanofluid coating I and hybrid nanofluid coating II have significant hydrophilicity, which helps to reduce water droplet accumulation and improve heat dissipation performance. Compared with the coatings with mature existing technologies (fluid test model IV and fluid test model V), the thermal conductivity of hybrid nanofluid coating I and hybrid nanofluid coating II is more than 30% higher than that of traditional coatings, which significantly improves the thermal conductivity, can effectively alleviate the problem of liquid hydrogen evaporation caused by temperature increase, can effectively block external heat (such as solar radiation, ambient temperature fluctuations, etc.) from being transmitted to the inside of the liquid hydrogen storage tank, and maintain the ultra-low temperature (-253℃) stability of the liquid hydrogen storage tank, thereby effectively preventing the pressure increase caused by temperature increase, liquid hydrogen evaporation and leakage and other safety hazards. At the same time, the coating exhibits excellent weather resistance and long-term stability in extreme low temperature environments, significantly improving the safety and reliability of the liquid hydrogen transportation process. It effectively reduces the temperature rise of the liquid hydrogen transport vehicle and reduces the evaporation loss, significantly improving the transportation safety and economy. In addition, hybrid nanofluid coating I and hybrid nanofluid coating II have excellent anti-corrosion properties. The thermal management ability and hydrophilicity of traditional alumina coatings are significantly reduced in extreme environments, and their stability is poor; while hybrid nanofluid coating I and hybrid nanofluid coating II can provide reliable corrosion protection under normal conditions, and can also maintain long-term stability and reliability in extreme environments such as low temperature, humidity and highly corrosive liquids, thereby significantly extending the service life of liquid hydrogen transport vehicles, while greatly improving the safety and economy of the transportation process.
[0058] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0059] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a hybrid nanofluid, characterized in that: The following steps are involved: Functionalizing multi-walled carbon nanotubes with sodium N-methyl-N-octadecyl taurate to obtain functionalized multi-walled carbon nanotubes; Adding bisaminopropyl polyether to the aqueous suspension of aluminum oxide, stirring, centrifuging and drying are performed in sequence to obtain stable aluminum oxide particles; The functionalized multi-walled carbon nanotubes, the stable aluminum oxide particles and titanium carbide are added into a base liquid and dispersed uniformly to obtain the hybrid nanofluid.
2. The preparation method according to claim 1, characterized in that: The base liquid is one of water and ethanol or a combination of the two; and / or, the mass ratio of the functionalized multi-walled carbon nanotubes, the stable alumina particles and the titanium carbide is 1:1-2:2-3; And / or, the uniform dispersion is achieved by ultrasonic treatment.
3. The preparation method according to claim 1, characterized in that: The functionalization treatment comprises the steps of: mixing the multi-walled carbon nanotubes with a 0.1 mol / L solution of sodium N-methyl-N-octadecyl taurate, sequentially performing ultrasonic dispersion, stirring at room temperature, suction filtration, and washing operations, and drying to constant weight to obtain the functionalized multi-walled carbon nanotubes; And / or, the preparation process of the stable alumina particles comprises the steps of: adding bisaminopropyl polyether to a suspension of alumina particles and deionized water in a mass ratio of 1:5, stirring at 300 rpm for 1 hour at 60°C, centrifuging, and drying to obtain the stable alumina particles.
4. A hybrid nanofluid, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 3.
5. A hybrid nanofluid coating, characterized in that: The preparation process includes the steps: The hybrid nanofluid, epoxy resin and bisaminopropyl polyether according to claim 4 are mixed, a dispersant is added, the mixture is dispersed evenly, and the solvent is evaporated at 50 to 70° C. to form a coating component A; Adding a curing agent, propylene glycol methyl ether, acrylic acid and polysiloxane into an organic solvent and uniformly dispersing them by ultrasonication to form a coating component B; The coating component A and the coating component B are mixed evenly to obtain the hybrid nanofluid coating.
6. The hybrid nanofluid coating according to claim 5, characterized in that: The dispersant is a nano-silane coating material; And / or, the curing agent is isocyanate; And / or, the organic solvent is ethanol; and / or, the mass ratio of the hybrid nanofluid, the epoxy resin, the bisaminopropyl polyether and the dispersant is 28:70:0.5:1.5; And / or, the mass ratio of the curing agent, the propylene glycol methyl ether, the acrylic acid and the polysiloxane is 20:3:0.7:0.5; And / or, the mass ratio of the coating component A to the coating component B is 7:
3.
7. Use of the hybrid nanofluid prepared by the preparation method according to any one of claims 1 to 3, the hybrid nanofluid according to claim 4, or the hybrid nanofluid coating according to any one of claims 5 to 6 in liquid thermal insulation storage and transportation equipment.
8. A liquid heat preservation storage and transportation equipment, characterized in that: Its outer surface is coated with the hybrid nanofluid coating according to claim 7; and the outer surface of the hybrid nanofluid coating is coated with a topcoat.
9. The liquid heat preservation storage and transportation equipment according to claim 8, characterized in that: The coating step of the hybrid nanofluid coating comprises: spraying at a pressure of 0.3 MPa and a thickness of 50 to 150 μm, and then drying at a temperature of 60° C. until the hybrid nanofluid coating is fully cured.
10. The liquid heat preservation storage and transportation equipment according to claim 8, characterized in that: The preparation steps of the topcoat include: mixing polyurethane resin with modified polyvinyl alcohol, adding a thickener and a solvent, and stirring at 60° C. for 1 hour to obtain the topcoat.
Citation Information
Patent Citations
Novel method for preparing water-based carbonaceous nano-tube nano-fluid
CN101343531A
Nanofluid for ammonia-water absorption refrigeration system and preparation method thereof
CN103113857A
High-heat conductivity coefficient water-based nanofluid and preparation method thereof
CN104164222A
Nano cycle working fluid for moderate-high temperature organic Rankine cycle and preparation method
CN105154026A
Method for preparing environment-friendly water-based metal color steel tile coating paint
CN105602400A
Cited By
Manufacturing process of liquid hydrogen storage tank with carbon-based anti-seepage coating on inner wall
CN121992331A